Reducing episodes of diabetic ketoacidosis within a youth population: a focus group study with patients and families. (December 2015) - Chafe, Roger; Albrechtsons, Daniel; Hagerty, Donna; Newhook, Leigh
Abstract Background Diabetic ketoacidosis (DKA) is the most common cause of morbidity and mortality for youth with type 1 diabetes mellitus (T1DM). This article reports qualitative data from focus groups with youth and parents of youth with T1DM on the barriers that they identify to DKA prevention and resources that may aid youth better manage their diabetes. Methods Four focus groups were held in three communities, two rural and one urban, in the Canadian province of Newfoundland and Labrador (NL) with adolescents and parents of youth with diabetes. Open-ended questions focused on knowledge of DKA, diabetes education, personal experiences with DKA, barriers to diabetes self-management, situations which put them at risk for DKA and resources that could be developed to aid youth in preventing DKA. Results There were 19 participants (14 parents and 5 youth). Participants identified factors which increased their risk of DKA as difficulty in distinguishing cases of DKA from other illnesses; variations in diabetes education received; information overload about their condition; the long period from initial diagnosis, when most education about the condition was received; and stress regarding situations where youth are not in the direct care of their parents. Participants from rural areas reported geographical isolation and lack of regular access to specialist health care personnel as additional barriers to better diabetes management. Conclusions The project identified barriers to DKA prevention for youth which were not previously identified in the medical literature, e.g., the stress associated with temporary guardians, risk of information overload at initial diagnosis and the long period from initial diagnosis when most diabetes education is received. Families from rural areas do report additional burdens, but in some cases these families have developed community supports to help offset some of these problems. Mobile and online resources, educational refreshers about DKA, concise resources for teachers and other temporary guardians, and DKA treatment kits for parents may help improve diabetes management and prevent future episodes of DKA.